Det syge USA: Afkoblede skæbner i litteraturen - Kongerslev, Marianne; Juncker, Clara (K&K - Kultur og Klasse, 2021)
Acknowledging the significance of the COVID-19 pandemic as an exacerbating factor for precarious US communities, this article reads Tony Kushner’s critically acclaimed play Angels in America: A Gay Fantasia on National Themes (1992-95) and Michael Henson’s collection of short stories Maggie Boylan (2015) alongside Susan Sontag (Illness as Metaphor), Jasbir Puar (The Right to Maim) and Lauren Berlant (“Slow Death”). The play and the short story collection represent examples of critiques of a deep-rooted disorder that characterizes the precaritizing American social and political system. From the severely mishandled AIDS crisis in Reagan’s conservative United States to the equally disastrous management of the opioid and meth epidemics in the 21st century, American society and politicians are failing their citizens, a failure reflected in and critiqued by literary texts. Whereas Angels in America is an overtly political drama, in which marginalized people come together to respond to political erasure and violence with imaginative countercultural utopianism, Maggie Boylan traces the gradual decay and corruption of a contemporary American community, functioning as a microcosm of the Unites States as a whole. This society is plagued by several crippling “epidemics” and “crises” that leave bodies broken and communities in tatters. Despite glimmers of hope, Kushner and Henson paint a grim picture of a sickness at the core of American society.